2021
DOI: 10.31577/sp.2021.01.815
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Partner Behavioral Control Scale (B-PBCS): Development and Validation

Abstract: Despite the large growth of close relationships literature, partner behavioral control has been rarely the primary focus of research. It is also evident that the instruments for measuring partner behavioral control are scarce. Thus, the present study aims to develop and validate a 9-item Brief Partner Behavioral Control Scale (B-PBCS). The validity and reliability of the B-PBCS were examined in a sample of emerging adults (N = 511; 81.8% females; Range age = 18-25) who are currently in a premarital romantic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…An example item is ‘I am happy to try new and challenging tasks’. Research results confirmed the unidimensional structure of the six-item short version of the MTS-A and provided good reliability coefficient (Sağkal & Özdemir, 2018b). Participants responded to a six-item scale on a 4-point Likert-type scale (1 = strongly disagree , 4 = strongly agree ), with higher scores indicating higher mental toughness.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…An example item is ‘I am happy to try new and challenging tasks’. Research results confirmed the unidimensional structure of the six-item short version of the MTS-A and provided good reliability coefficient (Sağkal & Özdemir, 2018b). Participants responded to a six-item scale on a 4-point Likert-type scale (1 = strongly disagree , 4 = strongly agree ), with higher scores indicating higher mental toughness.…”
Section: Methodssupporting
confidence: 63%
“…To assess adolescents’ mental toughness, the Mental Toughness Scale for Adolescents (MTS-A; McGeown et al, 2018) was used in this study. The MTS-A was first developed by McGeown et al (2018) and later revised by Sağkal and Özdemir (2018b). While the original scale comprises six subscales (commitment, challenge, control life, control emotions, confidence in abilities, and interpersonal confidence) and 18 items in total, Sağkal and Özdemir (2018b) in their Turkish validation study with 11- to 18-year-old school children tested the validity and reliability of a short-form version of the MTS-A that included the best exemplar items of the six dimensions.…”
Section: Methodsmentioning
confidence: 99%